Electrochemical Microphysiometry Detects Cellular Glutamate Uptake. Issue 12 (9th August 2018) - Miller, Dusty R.; McClain, Ethan S.; Cliffel, David E.
Abstract : Glutamate is the principal excitatory amino acid in the vertebrate nervous system and is responsible for learning and memory. Understanding of these complex biological processes can be gained through experimentally accessible systems of glutamate detection. In this work, the microclinical analyzer (μCA) was used with a sensitive and stable glutamate sensor and model neuronal cells for quantitative glutamate detection under physiological relevant shear. Glutamate was detected by immobilized glutamate oxidase on a screen-printed electrode array. The sensor's linear range spanned glutamate's physiological to pathophysiological concentration range, and the biologically relevant sub-second to month temporal range. After 11 hours of use, the sensor retained 91 ± 1% of its signal, and it was able to be stored for a month without a significant decrease. When model neuronal cells were integrated into the μCA bioreactor and exposed to glutamate, they initially took up 210 ± 100 μmoles of glutamate, which increased to 390 ± 50 μmoles during their second exposure. These data suggest that the neurotransmitter uptake systems were functional and may be upregulated. The dynamic and durable μCA platform offers an experimentally accessible system of glutamate detection that can be used to monitor glutamate metabolism and signaling.